Examining E-Learning Adoption Through the Lens of the Information Systems Success Model: An Empirical Study on Higher Education Institutions in Indonesia - Fitri Rostina Zaini Bustamam; H Hartini (Garuda Prestasi Nusantara Consulting, 2022)
Due to the outbreak of COVID-19, learning institutions in Indonesia have been forced to switch to e-learning. E-learning is a new way of education that everyone had to adopt. To ensure the continuity of teaching and learning activities, higher education institutions (HEIs) need to explore ways to increase the quality of e-learning systems. The paper aims to understand the quality factors that influence e-learning adoption in Indonesia. The proposed framework is validated with 753 students from four universities located in different regions of Indonesia. Data were analysed using Statistical Package for the Social Sciences (SPSS) software. The findings show that a relationship does exist between information quality and e-learning adoption. However, system and service quality did not indicate any significant influence on e-learning adoption. Keywords: Information Quality, System Quality, Service Quality, E-Learning Adoption